2021
DOI: 10.1002/pssr.202000481
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric Properties and Polarization Fatigue of La:HfO2 Thin‐Film Capacitors

Abstract: Recently, doped HfO2 thin films have attracted considerable attention because of promising applications in complementary metal–oxide–semiconductor (CMOS)‐compatible ferroelectric memories. Herein, the ferroelectric properties and polarization fatigue of La:HfO2 thin‐film capacitors are reported. By varying the substrate lattice constant and film thickness, a robust remanent polarization of ≈16 μC cm−2 is achieved in a 12 nm‐thick Pt/La:HfO2/La0.67Sr0.33MnO3 capacitor. Fatigue measurements are conducted using d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 55 publications
5
36
2
Order By: Relevance
“…[412,413] Therefore, the formation of large grains during the fabrication process may increase the number of cycles to fatigue. [414][415][416] Huang et al [412] showed that the domain-wall pinning caused by carrier injection at [315] Copyright 2021, ACS.…”
Section: Fatiguementioning
confidence: 99%
See 1 more Smart Citation
“…[412,413] Therefore, the formation of large grains during the fabrication process may increase the number of cycles to fatigue. [414][415][416] Huang et al [412] showed that the domain-wall pinning caused by carrier injection at [315] Copyright 2021, ACS.…”
Section: Fatiguementioning
confidence: 99%
“…[ 412,413 ] Therefore, the formation of large grains during the fabrication process may increase the number of cycles to fatigue. [ 414–416 ] Huang et al [ 412 ] showed that the domain‐wall pinning caused by carrier injection at shallow defect centers is the major fatigue mechanism of the HfO 2 ‐based ferroelectric materials. A fatigue‐free system was achieved by subsequent annealing, confirming the shallow trap characteristic of the domain wall pinning defects.…”
Section: Challenges Of Hfo2 In Emerging Nonvolatile Memory Devicesmentioning
confidence: 99%
“…(1-x)HfO 2 -xZrO 2 /Si(100) [75] HZO/LSMO/(001)STO [139] 800 0.1 18 20 No HZO/LSMO/LNO/CeO 2 /YSZ/Si(001) [57,102] 800 0.1 9.5 20 No HZO/LSMO/(001)STO [45] 800 0.1 6.9 24 No HZO/LSMO/STO [54,84]b) 800 0.1 1.5-27 34 No HZO/LSMO/(001)STO [139] 800 0.1 9, 18 20 No HZO/LSMO/(001)S [60,83,140,141]c) 800 0.1 9.5 5-25 -HLO/LSMO/(001)STO [142] 600 0.1 12 16 -HZLO/LSMO/(001)STO [38] 800 0.1 4.5-13 21-28 No HZLO/LSMO/STO/(001)Si [38] HZO/LSMO/STO/Si [55] 800 0.1…”
Section: Reference T S [ C] P O2 [Mbar] D [Nm]mentioning
confidence: 99%
“…However, a growing number of studies have reported the growth of epitaxial ferroelectric HfO 2 films. [387][388][389][390][391][392][393][394][395][396][397][398] One example is the epitaxial growth of 15-20 nm YO 1.5 -substituted HfO 2 films by pulsed laser deposition on [100]-oriented yttrium oxide-stabilized zirconium oxide (YSZ) substrates, 387 and on YSZ(110) single crystals using Sn-doped In 2 O 3 (ITO) as a bottom electrode, 389 where large ferroelectric polarizations and an estimated critical temperature of 723 K were observed. A cross-sectional annular bright field STEM image of a ca.…”
Section: Hfomentioning
confidence: 99%